We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
413
2
avatar+305 

Simplify

 

(3x2y3)(2xy2)2

       -2x2y

 Jan 30, 2017

Best Answer 

 #1
avatar+8139 
+5

(3x2y3)(2xy2)2

____________

       -2x2y

 

\(\Large \frac{(3x^2y^3)(2xy^2)^2}{-2x^2y}=\frac{(3x^2y^3)(4x^2y^4)}{-2x^2y}=-6x^2y^6\)

 

laugh  !

 Jan 30, 2017
 #1
avatar+8139 
+5
Best Answer

(3x2y3)(2xy2)2

____________

       -2x2y

 

\(\Large \frac{(3x^2y^3)(2xy^2)^2}{-2x^2y}=\frac{(3x^2y^3)(4x^2y^4)}{-2x^2y}=-6x^2y^6\)

 

laugh  !

asinus Jan 30, 2017
 #2
avatar+7445 
+5

\(\dfrac{\left(3x^2y^3\right)\left(2xy^2\right)^2}{-2x^2y}\\ =\dfrac{\left(3\cdot 2\right)\cdot\left(x^2\cdot x^2\right)\cdot\left(y^3\cdot y^4\right)}{-2x^2y}\\ =\dfrac{6x^4y^7}{-2x^2y}\\ =\left(\dfrac{6}{-2}\right)\left(\dfrac{x^4}{x^2}\right)\left(\dfrac{y^7}{y}\right)\\ =-3x^2y^6\)

 

~The smartest cookie in the world.

 Jan 30, 2017

7 Online Users

avatar